EFFECTS OF SILVER INDUSTRY WASTE WATER IN KOTAGEDE, YOGYAKARTA ON HAEMTOLOGlCAL AND HISTOPATHOLOGICAL CHANGES IN EXPERIMENTAL RATS (RATTUS NORVEGICUS) - Bambang Hariono (Jurnal Sain Veteriner, 1998)
Thirty male rats, 2,5 months old with average body weight of 92 grams were used as experimental animals.The experiment rats were adapted before for one week. The animal grouping was basedon uniformity of body weight gain, Thecontrol group consist of 15 animals and 15 animals for treated group. The treated group was given silver industry waste water from Kotagede, Yogyakana orally ad libitum the control group was supplied drinking tap water ad libitum. Blood samples via plexus retroorhitalis vein at medial cantus of the eye were taken for routine heamiolafiical examinations, clinical symptoms and body weight gain were also recorded. After treatment, for about 12 weeks, all experimental animals were sacrificed, necropsied, then the samples of brain, spinal cord, lung, tesiis. liver, and kidney were taken for histopathological preparations. The concentration of metals (especially Ag and Cu) in the liver, silver industry waste water, well water, Tap water, and soil samples (which [he silver industry waste water was discarded) were analyzed. The results of the experiment indicated thai the silver industry waste water administration in long period caused decreasing of the rat growth rate with clinical symptoms e.g. thinness,dullnessof the fur, anaemic, depression and nerve symptoms including foot paralysis. Statistical calculation showed there were not significantly changes on hematological profile between the control and treated groups, it could be due to severe dehydratation level occured, so there were reducing of blood volume. This finding was similar to leucocyte and differential counts, but there tended to decrease at week-12. There could be due 10 bone marrow depression which were caused by heavy metal intoxication. Microscopical examinaton showed there were thickness of alveoli septa, congestion, enlargement of sinusoids and infiltration of mononuclear cells around the liver centralvein, degeneration and necrosis of tubule cells, enlargement of tubule lumen and Bowman capsule space, infiltration of monoclear cells and haemorrhage performance. There were a few Purkinje cells showed more denses and the sTain more absorpted intensively (the same findings occuredin the nerve cells of spinal cord), it could be possible that there were cell structural changes, degeneration and necrosis of The nerve cells especially in the spinal cord tissues. The silver, copper and chrome concentrations in the silver industry waste water and soils samples were too high, it could be as potential sources for environmental pollution. The concentration of these metals in the tap water and well water were not detected yet.